2004
DOI: 10.1111/j.1467-9701.2004.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Diversity and Sources of Economic Growth in China

Abstract: Regional diversity in the process of economic growth is the major concern in this paper. We will try to identify its sources for growth and to specify production functions in each province by estimating translog production function. This paper clarifies the following four facts: First, capital accumulation was a major source for growth in the earlier stage of the Chinese economy, especially in the eastern coastal region. Unexpectedly, capital accumulation is losing its ground over the years. Second, the employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 6 publications
4
35
0
Order By: Relevance
“…Ganegodage and Rambaldi (2011) demonstrate that capital investment is the key driver of long-run economic growth. Chen and Fleisher (1996), Wei et al (2001), Arayama and Miyoshi (2004) also provide empirical evidences from China to support this viewpoint.…”
Section: Impacts Of Education On Economic Growthmentioning
confidence: 99%
“…Ganegodage and Rambaldi (2011) demonstrate that capital investment is the key driver of long-run economic growth. Chen and Fleisher (1996), Wei et al (2001), Arayama and Miyoshi (2004) also provide empirical evidences from China to support this viewpoint.…”
Section: Impacts Of Education On Economic Growthmentioning
confidence: 99%
“…Kim and Lau [ 6] applied the aggregate meta-production function framework and found that growth mostly resulted from the growth of tangible inputs, that is, capital and labor, and not technical progress or TFP. Other researchers later found that TFP was the primary driving force behind China's growth [7][8][9][10]. Borensztein and Ostry [ 11] believed China's technological progress was slow even though TFP made a remarkable contribution in the post-reform period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The decomposition result from Equation (8) suggests that economic growth with environment regulation is affected by these seven factors. The last five components, measure the effects on economic growth of changes in labor (LE), capital (KE), energy (EE), CO 2 emissions (CAE) and output structure (OSE) with environmental regulation, respectively.…”
Section: Green Growth Accounting Frameworkmentioning
confidence: 99%
“…In a vast country such as China, there are both historic and geographic reasons for regional differences in economic development [33][34][35]. Some eastern regions of China have already entered a stage of economic development comparable to moderately-developed countries, presenting a gradually stabilized energy consumption trend.…”
Section: Economic Aspectsmentioning
confidence: 99%